EKSTRAKSI DAN KARAKTERISASI PEKTIN DARI LIMBAH KULIT SEMANGKA MENGGUNAKAN EKSTRAK ENZIM Aspergillus niger - ZONA OCTARYA; AFNI RAMADHANI (Jurnal Agroteknologi, 2014)
Watermelon is a horticulture plant that much like by the general people. The sweet taste and high water content of watermelon often used as a food or beverage that is refreshing. The watermelon consumption produces waste including peel of watermelon. And the peel of watermelon contains a lot of useful components including pectin. Pectin is a polysaccharide compound that consist of galacturonate acid molecules. Pectin is widely used as a functional component in the food, pharmaceutical industries, feed industry. Pectin is usually extracted by strong mineral acids. The use of mineral acids can be dangerous if the pectin is processed into food and can cause environmental problems. This study aims to utilize waste as an alternative source of watermelon peel pectin extracted enzymatically by Aspergillus niger. In this research, there are some of procedure namely the enzyme production of  Aspergillus niger, pectinase enzyme extraction, hydrolysis enzymatically pectin and pectin powder manufacturing process consisting of coagulation, sedimentation, drying to obtain dry pectin. The results showed that pectin in this research namely low metoxyl pectin 6.24%, yield 15.26 %, moisture content 11.46 %, ash content 4.8 %, equivalent weight 789 mg, galacturonate content 57.72 % and degree of esterification 61.33 %.